Maternal Knowledge and Practices Concerning Infant Oral Health in a Group of Pregnant Women - Arias-Mendoza, Martha J. (2025)
To identify factors associated with the knowledge and practices of pregnant women regarding their children’s oral health. A cross-sectional study was conducted with 269 pregnant women attending two healthcare institutions in the Santander-(Colombia). A questionnaire was carried out, consisting of 40 questions (nine sociodemographic, seven on the psychosocial dimension [D], thirteen on knowledge [K], and eleven on practices [P]). Scoring scales were established for all dimensions, based on the Median (Me) and Interquartile Range (IQR). Descriptive analyses were performed, as well as normality tests on key variables, statistical significance tests, and multivariate linear regression analysis. 53.1% of participants were ≥ 26 years old. 78% lived in low socioeconomic strata. 12.6% were Venezuelan. Regarding questionnaire items, the dimensions showed high scores (D: Me=7, IQR=1; K: Me=9, IQR=4; PR: Me=6, IQR=3). Multivariate linear regression analysis revealed explanatory factors significantly associated with the questionnaire dimensions. For the psychosocial dimension, women from middle-high socioeconomic strata and those of Venezuelan origin were negatively associated (lower scores). For oral health knowledge, a positive association was found in women aged 27 or older (higher scores). For oral health practices, women without formal employment and multigravida women showed a positive association, whereas those with technical or higher education were negatively associated. Factors associated with knowledge, practices, and the psychosocial dimension were identified. These should be considered when designing oral health promotion strategies targeting the mother-child dyad.